The Method of Analyzing the Conceptual Components of Civilization - Sayyed Hossein Hosseini (حکمت معاصر, 2014)
Interdisciplinary nature of ‘researching civilization’ studies expands the domain of its issues from some certain specialized categories to a wider range. This challenge appears especially in the analyzing the concept of civilization more than anywhere else; because here we deal with a multidimensional word which carries another parallel concepts along with. Concepts like human, culture, society, history, religion, are considered as synonyms of the concept of civilization. So solving the problem of understanding the unreachable sides of the meaning of the word depends on the understanding the whole body of the synonymous words; on the one hand the conceptual realm of each word should be trimmed and on the other their pseudo-systems should be convoluted in order to we could reveal their relative impact on each other and achieve a systematic definition for the word. In the introduction, after pointing out the paper's aims in determining the conceptual components of civilization (rather than defining it), we will mention tripod assumptions of ‘non-realization of Islamic civilization in the modern world’ ‘necessity of establishing a modern Islamic civilization’ and ‘the possibility of such a civilization’. Then as a first step towards a systematic analysis of the problem, we talk about the ‘set-oriented’ model which looks systematically at par implications, and then by analyzing the relation between the civilization concept and four other terms we will provide a new interpretation of civilization. The privileges and five stages of the analysis, will constitute the next part of the paper, according to which and regarding the application of ‘Western Civilization’ in the world today, it is shown that the proposed model self-consistently is capable to analyze the current situation of the dominant civilization too, and that is why the paper talks about the appearance of a comprehensive analysis. Finally, based on the achieved concept and infused quality of the western civilization, this paper will try to reveal conceptual components of civilization. We will talk about the eight components: transnational dominance; collective and human will; ‘land and cradle’ element; geographic boundaries non-limitation; human relationships inclusion; influence and supremacy; seeking excellence, and the impact on historical developments. Finally through comparing the elements of the mentioned analysis, we will have a quick look on Islamic civilization concept